Gellan Gum Promotes the Differentiation of Enterocytes from Human Induced Pluripotent Stem Cells - Shimeng Qiu; Tomoki Kabeya; Isamu Ogawa; Shiho Anno; Hisato Hayashi; Tatsuro Kanaki; Tadahiro Hashita; Takahiro Iwao; Tamihide Matsunaga (MDPI AG, 2020)
The evaluation of drug pharmacokinetics in the small intestine is critical for developing orally administered drugs. Caucasian colon adenocarcinoma (Caco-2) cells are employed to evaluate drug absorption in preclinical trials of drug development. However, the pharmacokinetic characteristics of Caco-2 cells are different from those of the normal human small intestine. Besides this, it is almost impossible to obtain primary human intestinal epithelial cells of the same batch. Therefore, human iPS cell-derived enterocytes (hiPSEs) with pharmacokinetic functions similar to human intestinal epithelial cells are expected to be useful for the evaluation of drug absorption. Previous studies have been limited to the use of cytokines and small molecules to generate hiPSEs. Dietary fibers play a critical role in maintaining intestinal physiology. We used gellan gum (GG), a soluble dietary fiber, to optimize hiPSE differentiation. hiPSEs cocultured with GG had significantly higher expression of small intestine- and pharmacokinetics-related genes and proteins. The activities of drug-metabolizing enzymes, such as cytochrome P450 2C19, and peptide transporter 1 were significantly increased in the GG treatment group compared to the control group. At the end point of differentiation, the percentage of senescent cells increased. Therefore, GG could improve the differentiation efficiency of human iPS cells to enterocytes and increase intestinal maturation by extending the life span of hiPSEs.